PERLINDUNGAN LINGKUNGAN BERKELANJUTAN MELALUI PENANAMAN MANGROVE BERBASIS KEMITRAAN DENGAN KOMUNITAS KEMANGTER DI DESA LONTAR KABUPATEN SERANG - Wahyu Kartiko Utami; Laeli Nur Khanifah; Elly Nurlia (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
The preservation of coastal ecosystems has become a crucial global priority, particularly in areas facing severe degradation due to industrialization, population growth, and climate change. This community engagement project aims to promote sustainable environmental protection through mangrove planting in Lontar Village, Serang Regency, Banten Province. The program involved collaboration among local communities, the Kemangter Community, and the Department of Government Science at Sultan Ageng Tirtayasa University. The method consisted of observation, interviews, and direct mangrove planting, engaging 125 participants and planting approximately 150 mangrove seedlings along the coastal area. The results demonstrate that collaborative governance between academics and local communities enhances ecological restoration, fosters environmental awareness, and strengthens social and economic resilience. Mangrove planting not only protects coastal areas from abrasion and erosion but also supports community-based ecotourism and small-scale fisheries, providing long-term economic benefits. The partnership model integrates scientific knowledge with local wisdom, forming a holistic and participatory approach to conservation. In conclusion, this initiative proves that sustainable environmental protection can be achieved through community–academic collaboration that unites ecological restoration, social empowerment, and local economic development toward a more sustainable future.